# Solve for y cube root of 9y+5 = cube root of 5-6y

9y+53=5-6y3
To remove the radical on the left side of the equation, cube both sides of the equation.
9y+533=5-6y33
Simplify each side of the equation.
Multiply the exponents in ((9y+5)13)3.
Apply the power rule and multiply exponents, (am)n=amn.
(9y+5)13⋅3=5-6y33
Cancel the common factor of 3.
Cancel the common factor.
(9y+5)13⋅3=5-6y33
Rewrite the expression.
(9y+5)1=5-6y33
(9y+5)1=5-6y33
(9y+5)1=5-6y33
Simplify.
9y+5=5-6y33
Rewrite 5-6y33 as 5-6y.
Use axn=axn to rewrite 5-6y3 as (5-6y)13.
9y+5=((5-6y)13)3
Apply the power rule and multiply exponents, (am)n=amn.
9y+5=(5-6y)13⋅3
Combine 13 and 3.
9y+5=(5-6y)33
Cancel the common factor of 3.
Cancel the common factor.
9y+5=(5-6y)33
Divide 1 by 1.
9y+5=(5-6y)1
9y+5=(5-6y)1
Simplify.
9y+5=5-6y
9y+5=5-6y
9y+5=5-6y
Solve for y.
Move all terms containing y to the left side of the equation.
Add 6y to both sides of the equation.
9y+5+6y=5
Add 9y and 6y.
15y+5=5
15y+5=5
Move all terms not containing y to the right side of the equation.
Subtract 5 from both sides of the equation.
15y=5-5
Subtract 5 from 5.
15y=0
15y=0
Divide each term by 15 and simplify.
Divide each term in 15y=0 by 15.
15y15=015
Cancel the common factor of 15.
Cancel the common factor.
15y15=015
Divide y by 1.
y=015
y=015
Divide 0 by 15.
y=0
y=0
y=0
Solve for y cube root of 9y+5 = cube root of 5-6y

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top